Surgical Replacement of Prolapsed Cloaca in an Indian Tent Turtle (Pangshura tentoria circumdata) – A Case Report - Vishvakarma, Shashank; Bajaj, Nitin K; Khan, Asad; Dawar, Meenakshi; Verma, Anjul (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Chelonians are basically diapsids which come under the  class Reptilia of subphylum vertebrata. In reptiles they  are kept in the order of Testudines which comprises turtles,  terrapins and tortoises (Kuchling, 2012). The chelonian  cloaca has extensive physiological interactions with both  the bladder and large intestine, enabling fluid recycling,  especially in uricotelic and hibernating species. The Indian  tent turtle are vulnerable species and falls within appendix  II of CITES, according to IUCN. This species is found in large  rivers and in the small tributaries. This report presents a case  of successful surgical replacement of prolapsed cloaca in a tent turtle at VCC, Jabalpur (MP) with minor complications.
Keywords: Surgical Replacement; Prolapsed